Demographic Overview Kidney Failure Patients Chronicles of Living Hemodialysis at Bahteramas Regional General Hospital Southeast Sulawesi Province - Hikmah Fauziah; Laode Muhammadin Matahana; Muhammad Azwan; Rahayuni (Journal of Epidemiology and Health Science, 2026)
Background:Chronickidneyfailure(CKD)isaglobal medical problemwhoseprevalenceisalwaysincreasingandoftenrequiresothermeasuresonthekidneys,suchUShemodialysis. Objective:Thisstudywasconductedtofindoutanddescribe the demographiccharacteristics of GGKpatientsundergoinghemodialysistherapyatBahteramasHospital,SoutheastSulawesiProvince,in2024. Methods: This study adopts a descriptive design with a quantitative approach, using secondary data derived from patient medical records. A total of 308 patients who met the inclusion and exclusion requirements were included in the sample. Results: According to the findings of the research, mostpatientsbelongtothelatetoadvancedadultagegroup,with a greaternumberofmalepatientsthanwomen.Mostpatientshaveasecondaryeducationlevelandworkin the privateandinformalsectors.Basedonthelengthoftreatment they have , the majorityofpatientsareinaperiodof1-3yearswhichindicatestheadaptationphasetothehemodialysisprocedure. Conclusion: Patients with chronic kidney failure at Bahteramas Hospital are dominated by middle- aged to advanced age groups, male, well educated, and working in the informal sector. Improved health education, routine monitoring, and social support are needed to maintain quality of life and prevent long-term complications. Keywords: Chronic Kidney Failure, Hemodialysis, Education, Prevalence, Medical Record Keywords: Chronic Kidney Failure; Hemodialysis; Patient Characteristics; Education; Employment